Clinical evaluation and finite element analysis of bone cement-augmented anterolateral screw fixation versus percutaneous bilateral pedicle screw fixation co-applied with oblique lumbar interbody fusion for single-level lumbar degenerative diseases with osteoporosis - Mu, Xiaoping; Wei, Xiaodong; Nong, Jiahong; Ye, Huabao; Li, Zhuhai; Wei, Minke; Wei, Jianxun (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundAs the population ages, there is an increasing trend in patients with lumbar degenerative diseases (LDD) complicated by osteoporosis seeking lumbar fusion surgery. However, standardized strategies for minimally invasive surgical procedures among these populations still need improvement in clinical practice.PurposeThis study was to integrate clinical and biomechanical approaches to investigate and demonstrate the effectiveness of oblique lateral interbody fusion combined with bone cement-augmented anterolateral screw (OLIF-BCAAS) in such patients.Study DesignA single-center, retrospective case-controlled clinical study and finite element model (FEM) analysis.MethodsA single-center, retrospective case-controlled clinical study and finite element model (FEM) analysis were conducted. 48 cases were enrolled in the clinical study, then assigned to either OLIF-BCAAS or OLIF combined with posterior internal fixation with pedicle screws (OLIF-PIFPS). Clinical outcomes and radiological parameters were statistically analyzed. The FE models of intact lumbar spine, OLIF-BCAAS, and OLIF-PIFPS were constructed based on computed tomography (CT) scans of a healthy male. These FE models were analyzed under different loading conditions.ResultsThere were significant differences in the surgical time, blood loss, and lower back score within 1 year postoperatively between the two groups (p < 0.05). Moreover, both OLIF surgical techniques showed significant improvements in disc height (DH) postoperatively; however, the reduction in DH at postoperative 12 months was more pronounced in the OLIF-PIFPS group than in the OLIF-BCAAS group (p < 0.05). Five cases (5/23, 21.74%) of cage subsidence (CS) were detected in the OLIF-BCAAS group, with 4 out of 23 cases (17.39%) considered as mild CS. In contrast, the amount of CS was 12 cases (12/25, 48%) in the OLIF-PIFPS group, which included 3 cases of severe CS. However, there was a trend towards statistical difference in CS between the two groups (p = 0.057). The FEM analysis showed significant reductions in the local range of motion and L3 maximum displacement with respect to L4 under six motion patterns in the two OLIF surgical models. Moreover, stress on the endplate and cage in the OLIF-BCAAS model was higher than that in the OLIF-PIFPS model; however, stress on the supplemental fixation devices was significantly lower than that observed in the OLIF-PIFPS model.ConclusionBoth OLIF surgical techniques for treating LDD with osteoporosis can achieve favorable clinical outcomes. However, OLIF-BCAAS exhibits more significant advantages over OLIF-PIFPS by maximizing the benefits of minimally invasive surgery. Moreover, OLIF-BCAAS is associated with lower postoperative back pain and a reduced incidence of postoperative CS.